Motivation of Police Cadets in Learning English for General and Specific Purposes - Oktania, Nesia; Hartono, Rudi; Aquariza, Novi Rahmania; Sulistiono, Agus (Biormatika : Jurnal ilmiah fakultas keguruan dan ilmu pendidikan, 2026)
Motivation is commonly accepted as a significant determinant in second language achievement. Different types of English courses may influence learners’ motivation. This study investigates the types of motivation evident among Indonesian Police Academy cadets learning English either for General Purposes or for Specific Purposes, as perceived by both cadets and teachers. Using quantitative survey methods, the research includes 100 cadets, equally divided into two groups and two teachers. Results indicate that both groups exhibit predominantly intrinsic and instrumental motivation. Cadets learning English for General Purposes display stronger motivation than cadets studying English for Specific Purposes. Teacher perspectives generally mirror these findings, although some nuances in motivation type are observed. Implications highlight the need for English for Specific Purposes curricula to bolster student-centeredness and relevance, thereby maximizing cadet motivation.